Clinical Utilization Pattern of Liquid Biopsies (LB) to Detect Actionable Driver Mutations, Guide Treatment Decisions and Monitor Disease Burden During Treatment of 33 Metastatic Colorectal Cancer (mCRC) Patients (pts) at a Fox Chase Cancer Center GI Oncology Subspecialty Clinic - Ghatalia, Pooja; Smith, Chad H.; Winer, Arthur; Gou, Jiangtao; Kiedrowski, Lesli A.; Slifker, Michael; Saltzberg, Patricia D.; Bubes, Nicole; Anari, Fern M.; Kasireddy, Vineela; Varshavsky, Asya; Liu, Yang; et al. (Frontiers in Oncology, 2019)
Background: Liquid biopsy (LB) captures dynamic genomic alterations (alts) across metastatic colorectal cancer (mCRC) therapy and may complement tissue biopsy (TB). We sought to describe the utility of LB and better understand mCRC biology during therapy. Methods: Thirty-three patients (pts) with mCRC underwent LB. We used permutation-based t-tests to assess associations between alts, and clinical variables and used Kendall’s tau to measure correlations. Results: Of 33 pts, 15 were women; 22 had colon and the rest rectal cancer. Pts received a median of 2 lines of therapy before LB. 19 pts had limited testing on TB (RAS/RAF/TP53/APC), 11 extended NGS and 3 no TB. Maxpct and alts correlated with CEA (p<0.001, respectively). In 3/5 pts with serial LB, CEA correlated with maxpct trend and CT tumor burden. In 6 pts mutant RAS was seen in LB and not TB; 5/6 had received anti-EGFR therapy prior to LB, suggesting RAS alts developed post-therapy. In 2 pts RAS-mutated by TB, no RAS alts were detected on LB; these pts had low disease burden on CT at time of LB that also did not reveal APC or TP53 alts. In 6 patients who were KRAS wt based on TB, post anti-EGFR LB revealed subclonal KRAS mutations, likely a treatment effect. The median number of alts was higher post anti-EGFR LB (n=12) vs anti-EGFR naïve LB (n=22) (9.5 vs 5.5, p=0.059) but not statistically significant. More alts were also noted in post anti-EGFR therapy LB vs KRAS wt anti-EGFR-naïve LB (n=6) (9.5 vs 5) among patients with KRAS wild-type tumors, although the difference was not significant (p=0.182). Conclusions: LB across mCRC therapy detects driver mutations, monitors disease burden, and identifies sub-clonal alts that reflect drug resistance, tumor evolution and heterogeneity. Interpretation of LB results is impacted by clinical context.